Addition of bevacizumab to EGFR tyrosine kinase inhibitors in advanced NSCLC: an updated systematic review and meta-analysis - Zheng, Haosheng; Qin, Xianyu; Zheng, Yuzhen; Yang, Xingping; Tan, Jian; Cai, Weijie; He, Shiyun; Liao, Hongying (Frontiers in Pharmacology, 2024)
The synergistic effects of antiangiogenic inhibitor bevacizumab and epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKI) therapy were encouraging in patients with EGFR-mutant advanced NSCLC, though some controversy remains. The specific subgroup of patients who might benefit most from the EGFR-TKI and bevacizumab combination therapy is yet to be determined.Randomized clinical trials (RCTs) that had compared the clinical efficacy of EGFR-TKI and bevacizumab combination therapy with EGFR-TKI monotherapy in treating EGFR-mutant advanced NSCLC patients published before December 23 rd , 2022 were searched in the Cochrane, PubMed and Embase. We performed a meta-analysis for the overall survival (OS), progression free survival (PFS), objective response rate (ORR), and treatment-related adverse events with a grade equal or more than 3 (grade≥3 TRAEs). Subgroup analyses of PFS and OS stratified by clinical characteristics and treatment were conducted.We included 10 RCTs involving 1520 patients. Compared with EGFR-TKI monotherapy, addition of bevacizumab to EGFR-TKI resulted in a significantly higher PFS (hazard ratio (HR)=0.74, 95% confidence interval (95%CI): 0.62-0.87)) and ORR (risk ratio (RR)= 1.07, 95%CI:1.01-1.13). However, no significant difference in OS (HR=0.96, 95%CI: 0.83-1.12) was noticed.Patients with EGFR-mutant advanced NSCLC receiving combination therapy showed PFS improvement regardless of gender (male or female), Eastern Cooperative Oncology Group performance status (0 or 1), baseline central nerve system (CNS) metastasis (presence or absence) and EGFR mutation type (19del or 21L858R). Subgroup analyses showed that, with the treatment of bevacizumab and EGFR-TKI, patients who ever smoked achieved significantly better OS and PFS benefits (HR=0.68, 95%CI: 0.48-0.95; HR=0.59, 95%CI: 0.46-0.74, respectively), and those aged <75 years and the Asian population had significantly prolonged PFS (HR=0.69, 95%CI: 0.52-0.91; HR=0.71, 95%CI: 0.58-0.87; respectively). The superiority of EGFR-TKI and bevacizumab combination therapy against EGFR-TKI monotherapy in improving PFS was more significant in the erlotinib regimen subgroup. The risk of grade≥3 TRAEs was remarkably higher in the combination therapy group (HR=1.73, 95%CI: 1.39-2.16).Addition of bevacizumab to EGFR-TKI therapy provided significantly better PFS and ORR for EGFR-mutant advanced NSCLC patients, though with higher risk of grade≥3 TRAEs.Patients who ever smoked, aged <75 years, and Asian population might benefit more from the combination regimen.